O currículo como percurso de reconhecimento da identidade negra: políticas e práticas curriculares no Instituto Federal de Educação, Ciência e Tecnologia do Maranhão (IFMA); Campus Monte Castelo - Pereira, Sueli Borges (2013)
The current Doctorate thesis has as its goal to analyze the policies and curricular practices at IFMA Monte Castelo Campus from the point view of ethnic-racial recognition. It has been considered as hypothesis that such policies and practices had not been sufficiently effective, critic, consistent, coherent and satisfactory, for the ethnic-racial recognition. It is particularly remarkable that São Luis has a history connected to slavery, a rich African descendant culture and a significant number of black population. It is adopted as analytic instrument the concept of mutual recognition, taken from Paul Ricoeur. The research has support on documental databases and it develops itself through a qualitative approach, where it has been used as a data collection instruments like detailed questionnaires, semi-structured interviews and informal observations. The thesis is built up on five chapters. In the first chapter, it describes the research‟s theoretical-methodological path. In the second one, it handles the ethnicity/race issue in educational scenery of Maranhão State. In the third chapter it delineates the relationships between human rights, human dignity and education. In the fourth chapter it handles the recognition as a concept and curricular politics. In the fifth chapter, analyses the obtained results from the field‟s research, discussing with the interviewed people the policies and curricular practices as well as some proposed indicators the light of ethnic-racial recognition, interculturality, Africanness and mutuality perspective. It is expected with this study to contribute with IFMA and other similar institutions in order to become policies references for curricular practices on affirmation and ideal recognition, mainly for black students